Day 3 Wed, June 27, 2018 2018
DOI: 10.2118/191274-ms
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient Imbibition Fracturing for Tight Oil Reservoir

Abstract: In view of tight oil reservoirs with no natural productivity (tight sandstone and carbonate reservoirs with matrix permeability under overburden pressure of no more than 0.2mD (pore permeability less than 2mD)), a nanometer high efficient oil washing agent has been developed by combining nano-drop, high efficient oil washing surfactant and wettability reversal means, which can turn the disadvantage of the small pores and throats into advantage and realize fracturing effect enhancement by making use of the spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Then, the control ranges of different saturation were calculated to obtain the fluid volumes in the core slices at different times. The formula for calculating the imbibition retention rate is where η is the imbibition retention rate, %; V r is the imbibition retention volume of water phase, m 3 ; and V Ф is the total pore volume of core slices, m 3 .…”
Section: The Process Of Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the control ranges of different saturation were calculated to obtain the fluid volumes in the core slices at different times. The formula for calculating the imbibition retention rate is where η is the imbibition retention rate, %; V r is the imbibition retention volume of water phase, m 3 ; and V Ф is the total pore volume of core slices, m 3 .…”
Section: The Process Of Experimentmentioning
confidence: 99%
“…Imbibition refers to the process that the wetting fluid spontaneously sucks into the pores and displaces the nonwetting fluid under the action of capillary force [1][2][3]. The concept of displacement can be divided into broad sense and narrow sense.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous imbibition of fracturing water into the matrix was considered as a possible mechanism to improve oil production [26,27]. Extensive experimental and mathematical studies were devoted to explaining the oil displacement efficiency by water imbibition with various rock wettabilities, physical parameters, pore size distribution, and fracture characteristics [28][29][30]. The results showed that water imbibition could drive oil out of the matrix pore, and the displacement effect would be better when the tight rocks contained fractures [29].…”
Section: Introductionmentioning
confidence: 99%